1950 MHz radiofrequency electromagnetic fields do not aggravate memory deficits in 5xFAD mice. Issue 6 (19th July 2016) - Son, Yeonghoon; Jeong, Ye Ji; Kwon, Jong Hwa; Choi, Hyung‐Do; Pack, Jeong‐Ki; Kim, Nam; Lee, Yun‐Sil; Lee, Hae‐June
Abstract : The increased use of mobile phones has generated public concern about the impact of radiofrequency electromagnetic fields (RF‐EMF) on health. In the present study, we investigated whether RF‐EMFs induce molecular changes in amyloid precursor protein (APP) processing and amyloid beta (Aβ)‐related memory impairment in the 5xFAD mouse, which is a widely used amyloid animal model. The 5xFAD mice at the age of 1.5 months were assigned to two groups (RF‐EMF‐ and sham‐exposed groups, eight mice per group). The RF‐EMF group was placed in a reverberation chamber and exposed to 1950 MHz electromagnetic fields for 3 months (SAR 5 W/kg, 2 h/day, 5 days/week). The Y‐maze, Morris water maze, and novel object recognition memory test were used to evaluate spatial and non‐spatial memory following 3‐month RF‐EMF exposure. Furthermore, Aβ deposition and APP and carboxyl‐terminal fragment β (CTFβ) levels were evaluated in the hippocampus and cortex of 5xFAD mice, and plasma levels of Aβ peptides were also investigated. In behavioral tests, mice that were exposed to RF‐EMF for 3 months did not exhibit differences in spatial and non‐spatial memory compared to the sham‐exposed group, and no apparent change was evident in locomotor activity. Consistent with behavioral data, RF‐EMF did not alter APP and CTFβ levels or Aβ deposition in the brains of the 5xFAD mice. These findings indicate that 3‐month RF‐EMF exposure did not affect Aβ‐related memory impairment or Aβ accumulation in the 5xFAD Alzheimer's disease model. Bioelectromagnetics. 37:391–399, 2016. © 2016 The Authors Bioelectromagnetics published by Wiley Periodicals, Inc. on behalf of Bioelectromagnetics Society.